Development of novel monoclonal antibodies for evaluation of transmembrane prostate androgen-iInduced protein 1 (TMEPAI) expression patterns in gastric cancer - Karbyshev, Mikhail S.; Kzhyshkowska, Julia (Pathology & oncology research, 2018)
Transmembrane prostate androgen-induced protein 1 (TMEPAI) is a single-span membrane protein, functionally involved in transforming growth factor beta signaling pathway. The particular protein presented in cells in three isoforms, which differs in the length of the soluble N-terminal extracellular domain, making it challenging for the immunochemical recognition. By using quantitative real-time polymerase chain reaction, we identified significant upregulation of PMEPA1 gene expression in malignant tissues of patients with gastric adenocarcinoma. The main part of commercially available anti-TMEPAI antibodies are having polyclonal nature or not suitable for immunocytochemical localization of target protein in tissue specimens. Hence, we decide to generate a set of novel rat monoclonal antibodies (mAb) directed against conservative C-terminal cytoplasmic epitope. Immunoblotting analysis showed that monoclonal antibodies, 2E1, 6C6, and 10A7 were able to recognize specifically target protein in transiently transfected HEK293T and CHO-K1 cells. Especially established mAb, named 10A7, showed the excellent binding ability to target protein in immunohistochemistry. By using developed antibodies, we observed pronounced expression of TMEPAI in normal gastric epithelial cells while tumor cells from gastric adenomas, and adenocarcinoma samples were mostly negative for target protein expression. Also, we found that gastric epithelium cells lose the TMEPAI expression concurrently with severe dysplasia progression, which probably caused by a mechanism involving specific microRNA.
Published online: 5 June 2017
Gesehen am 26.06.2018